The Role of Emotional Intelligence in Effective Leadership: A Review - Sidrotun Na'im; Feri Irawan; Ahamd Zain Sarnoto; Windy Dian Sari; Rembe, Elismayanti; Aat Ruchiat Nugraha; Nursalim, Eko; Santosa, Tomi Apra; Diah Fatma Sjoraida; Rahmah, Andi (Asosiasi Ide Bahasa Kepri, 2024)
Effective leadership is often associated with a variety of competencies and personal characteristics, where emotional intelligence (EI) has been a major focus in the last decade. This study examines the role of emotional intelligence in effective leadership through a comprehensive literature review. Using a systematic approach, we analyzed relevant articles and books from 2022 to 2024, which included theory, empirical research, and case studies on EI and leadership. The results of this review show that EI contributes significantly to effective decision-making, conflict management, and the development of interpersonal relationships in the context of leadership. Furthermore, emotional intelligence allows leaders to be more effective in managing stress and motivating subordinates. These findings underscore the importance of integrating EI training in leadership development programs to improve leadership effectiveness in various sectors. The study proposes several recommendations for leadership practices and future research directions, reinforcing the view that EI is an essential key to successful and sustainable leadership